2017
DOI: 10.1016/j.jnutbio.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of fibroblast growth factor 2 and its co-receptors heparan sulfate proteoglycans by resveratrol underlies the improvement of cardiac dysfunction in experimental diabetes

Abstract: Cardiac remodeling in diabetes involves cardiac hypertrophy and fibrosis, and fibroblast growth factor 2 (FGF2) is an important mediator of this process. Resveratrol, a polyphenolic antioxidant, reportedly promotes the improvement of cardiac dysfunction in diabetic rats. However, little information exists linking the amelioration of the cardiac function promoted by resveratrol and the expression of FGF2 and its co-receptors, heparan sulfate proteoglycans (HSPGs: Glypican-1 and Syndecan-4), in cardiac muscle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…32 In a recent study, the role of FGF basic was suggested in type 2 diabetic rats where upregulation of expression of FGF basic proteins were shown. 33 In that study, resveratrol promoted the attenuation of left ventricular diastolic dysfunction by decreasing FGF basic. MMP-9 is a dysglycaemia marker 34 that fits with an early stage of cardiovascular disease as MMPs are synthetized in atherosclerotic plaques, and MMP activity is correlated with unstable angina and plaque rupture.…”
Section: Discussionmentioning
confidence: 84%
“…32 In a recent study, the role of FGF basic was suggested in type 2 diabetic rats where upregulation of expression of FGF basic proteins were shown. 33 In that study, resveratrol promoted the attenuation of left ventricular diastolic dysfunction by decreasing FGF basic. MMP-9 is a dysglycaemia marker 34 that fits with an early stage of cardiovascular disease as MMPs are synthetized in atherosclerotic plaques, and MMP activity is correlated with unstable angina and plaque rupture.…”
Section: Discussionmentioning
confidence: 84%
“…T1DM was modeled with a single injection of STZ (50 mg/kg, Sigma-Aldrich, St. Louis, MO, USA) dissolved in citrate buffer (0.01 M, pH 4.5) as previously described [23]. Glucose blood levels and body weights were measured after a 4-hour fasting period.…”
Section: Stz Injection and Blood Glucose Level Measurementmentioning
confidence: 99%
“…In fact, we found enrichment for AMPK regulatory mechanisms including ATP and adenyl ribonucleotide signalling, for AMPK-dependent classical metabolic pathways such as carbohydrate, amino acid metabolism 39,47,49,50 , and for adipocytokine signalling 51,52 .…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, several of these signalling pathways previously implicated in axonal regeneration have been found to be regulated by AMPK. They include neurotrophin, insulin, mTOR, JAK-STAT, MAPK, ErbB and VEGF signalling [26][27][28][43][44][45][46] , while others are related to AMPK-dependent metabolic regulation such as carbohydrate, amino acid metabolism 26,[47][48][49][50] or adipocytokine signalling 51,52 .…”
Section: Combinatorial Axoplasmic Proteomics and Rnaseq From Drg Suggmentioning
confidence: 99%